2011
DOI: 10.1021/nn1035697
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Imprinted Mesoporous Organosilica

Abstract: We have prepared molecularly imprinted mesoporous organosilica (MIMO) using a semicovalent imprinting technique. A thermally reversible covalent bond was used to link a bisphenol A (BPA) imprint molecule to a functional alkoxysilane monomer at two points to generate a covalently bound imprint precursor. This precursor was incorporated into a cross-linked periodic mesoporous silica matrix via a typical acid-catalyzed, triblock copolymer-templated, sol-gel synthesis. Evidence of imprint sites buried in the pore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 26 publications
1
65
0
Order By: Relevance
“…2a, the broad hysteresis in the isotherm of MIMS-2 indicates a less ordered mesoporous material with a smaller pore size (4.8 nm) than that of PMS (5.1 nm). This is in accordance with the trend of imprinted mesoporous silica reported by Lofgreen et al [12]. NIMS was made by pre-hydrolysis solgel process to avoid the interruption of the amino groups from the silica matrix to the surfactant template [19].…”
Section: Nitrogen Adsorption/desorption Characterizationsupporting
confidence: 89%
See 2 more Smart Citations
“…2a, the broad hysteresis in the isotherm of MIMS-2 indicates a less ordered mesoporous material with a smaller pore size (4.8 nm) than that of PMS (5.1 nm). This is in accordance with the trend of imprinted mesoporous silica reported by Lofgreen et al [12]. NIMS was made by pre-hydrolysis solgel process to avoid the interruption of the amino groups from the silica matrix to the surfactant template [19].…”
Section: Nitrogen Adsorption/desorption Characterizationsupporting
confidence: 89%
“…The template precursors of 2-naphthol (1) and 2,7-dihydroxylnaphthalene (2) were prepared according to published procedure [12]. Phenol moieties were reacted with a stoichiometric amount of (3-isocyanatopropyl) Molecularly imprinted mesoporous silicates (MIMSs) were prepared by a triblock-copolymer-templated solgel method.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…60 Studies of sensing and imprinting using PMOs have been reported by several researchers for the removal of organic molecules and metal ions. [61][62][63][64][65][66][67] Riley and co-workers 61 prepared a PMO material with imprinted sites for selective benzene adsorption. They compared their results with those obtained from non-imprinted adsorbents to highlight the importance of the imprinting effect.…”
Section: Pmo Materials As Hosts For Drug and Biomoleculesmentioning
confidence: 99%
“…3-Isocyanatopropyltriethoxysilane (IPTES), APTES and pluronic P123 (EO 20 PO 70 EO 20 , MW ¼ 5800 Da) were purchased from Sigma Chemical Co., St. Louis. All other chemicals used were of analytical grade.…”
Section: Chemicals and Materialsmentioning
confidence: 99%